Pelimpahan Wewenang Ajaran â€œHisbahâ€ di Indonesia - Asnawi, M. Nur (ULUL ALBAB Jurnal Studi Islam, 2005)
The style o f government which was used by prophet Muhammad SAW attention to good intellectvalue. He ordered“Amar Ma’ruf Nahi Munkar" in every aspect include in economics. Hisbah one o f the institute that control o f social live in general is known with main mission as commerce. There isn ’t in Indonesia league, bui systematic it is efective although there are marry kind of modification. The control league in Indonesian is operated by various department. We can find them in National Education Department, Relegious Department, Security Department, Commerce and lndustry Department, etc. All of them have to control the problem fitting with their area.